Methodological Aspects of Determining the Effectiveness of Management Segment Accounting and Reporting in Cotton-Textile Clusters - Luptullaevich, Khalikov Talibjon (Indonesian Journal Publisher, 2025)
This study looks at the challenges of using segmental accounting and reporting in Uzbekistan's cotton and textile clusters. While acknowledging the critical role these clusters play in economic modernization and export growth, the report also highlights a substantial knowledge gap on the practical application of segment accounting standards. Using financial analysis and economic-statistical methodologies, the research assesses the effectiveness of weaving machines and offers recommendations for improving segment reporting protocols. The findings indicate that global segment accounting rules can greatly boost transparency and investor confidence. Therefore, the article suggests that governments and industry stakeholders should speed the implementation of these standards in order to assist economic development and enhance competitiveness in the global market.